Dublin core and museum information: metadata as cultural heritage data. (7th February 2007) - Nevile, Liddy; Lissonnet, Sophie
In 2000, the museum community reported on the use of Dublin Core metadata in the museum context and proposed a broader set of elements for museums. Since then, Dublin Core metadata has evolved and it is now possible to use rich descriptions (data) and Semantic Web technologies and maintain the interoperability of Dublin Core metadata. This paper reviews the museum experience in the light of developments in the DCMES. It is based on recent experience with a virtual museum of Indigenous culture using Metadata Application Profiles (MAPs) and schema cross-walks.